Survival of the fittest - Caires, Filipe B. (2023)
Funding Information: The authors thank two anonymous referees and Editor Mark P. Taylor for their helpful and constructive feedback on an earlier version of this paper. Rodrigues gratefully acknowledges financial support from the Portuguese Science Foundation (FCT) through (UID/ECO/00124/2013 and Social Sciences DataLab, Project 22209), POR Lisboa (LISBOA-01-0145-FEDER-007722 and Social Sciences DataLab, Project 22209) and POR Norte (Social Sciences DataLab, Project 22209). Publisher Copyright: © 2023 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.